Understanding the dietary behaviours of male academy football players: using the nominal group technique to select and specify target behaviour(s) - Roe, S.; Costello, N.; Backhouse, S.; Bentley, M. (International Journal of Sport Nutrition and Exercise Metabolism, 2024)
An integral role of a sports nutritionist is to design and deliver effective dietary interventions. However, many academy players fail to meet energy and carbohydrate recommendations, thus limiting their growth, development, health, and performance. Guided by the Behaviour Change Wheel, this case study utilised the Nominal Group Technique (NGT) to select and specify the dietary behaviours that nutrition practitioners should target in sports nutrition interventions to enable male academy football players to achieve their dietary requirements. Two NGT workshops (mean duration = 2 hour 20 minutes) were conducted with four sports nutritionists (male = 3, female = 1) who were currently working at an English Football League Championship Football Club (n = 3), or who had previously worked at the club within two years (n = 1). During the workshops, participants were asked to 1) identify the dietary behaviours that enable male academy players to meet their nutritional requirements and 2) rank the dietary behaviours by importance. The workshops facilitated a co-production of behaviours to enable within male academy footballers. The three most important behaviours agreed by nutritionists included: 1) consume at least three main meals and two snacks per day, 2) consume at least three to four portions of carbohydrate per main meal and one portion per snack, and 3) consume a portion of protein during at least four eating occasions per day. During the workshops, some challenges were observed, including difficulties transferring nutritional recommendations into athlete behaviours, as practitioners were unfamiliar with the agreed definition of a "behaviour" by the behavioural science field. Despite this, the structured NGT approach would allow future involvement of stakeholder voice, whilst benefitting as a prioritisation tool for sports nutritionist`s professional practice. This project highlights the benefit of using NGT within a high-performance environment for reaching consensus on the dietary behaviours to be enabled within male academy football players. The acquired knowledge and understanding will guide an exploration of the target behaviours, and in turn, inform the development of a theoretically driven nutrition intervention seeking to protect athlete health, wellbeing, and performance.